Analisis Asuhan Keperawatan pada Pasien Post Operasi Sectio Caesarea dengan Masalah Nuasea dengan Pemberian Akupresure - Werdiyana, Nyoman Gading; Prihandini, Claudia Wuri; Sukmandari, Ni Made Ari (STIKes Hamzar, 2025)
Postoperative nausea and vomiting is one of the side effects that often occurs in the first 24 hours after SC surgery, mostly due to the influence of anaesthetic drugs.Prevention and treatment of nausea and vomiting can use complementary therapies such as acupressure. Acupressure has the advantage that acupressure has the principle of healing touch. This Ners Final Scientific Work was carried out to determine the analysis of nursing care in postoperative sectio caesarea patients with nuasea problems by giving acupressure. The results of the assessment obtained the main complaints of the three managed patients were that the patients said they complained of nausea, felt like vomiting and there was a sensation of swallowing frequently, the nursing plan provided acupressure, nursing action by giving acupressure was carried out 2 times for 15 minutes each. The results of the nursing evaluation carried out in the three cases of management showed that all of them felt more comfortable, the patient said the sensation of frequent swallowing began to decrease, the patient said the nausea decreased, the patient said the feeling of wanting to vomit decreased It is recommended that nursing services can be used as evidence-based practice in the preparation of standard operating procedures in hospitals regarding the provision of acupressure at point P6.